Microbial Consortia in the Remediation of Single-Use Waste: The Case of Face Masks - María del Refugio Castañeda Chávez; Luz María Campos García; Christian Reyes Velázquez; Fabiola Lango Reynoso; David Reynier Valdés; Isabel Araceli Amaro Espejo; Gabycarmen Navarrete Rodríguez (Microbiology Research, 2024)
This study presents the results of evaluating hydrocarbonoclastic consortia in the biodegradation of microplastics derived from single-use, triple-layered polypropylene face masks. The choice of this carbon source was driven by the need to address the increase in single-use waste generated during the recent SARS-CoV-2 pandemic, as the use of face masks was a mandatory protective measure. Two bubble column bioreactors were used, each containing hydrocarbonoclastic consortia sourced from the Port of Veracruz and the Gulf of Mexico. The biodegradation activity of these consortia was assessed by observing the physical appearance of microplastic samples under a stereoscope and a microscope, as well as by calculating the weight loss of polypropylene after 15 days. The results revealed that the consortium from the Gulf of Mexico, with a maturity of 1 year, showed a higher capacity for polypropylene biodegradation, achieving a 19.98% degradation rate. This consortium also demonstrated more stable kinetics during the experimentation period. In contrast, the younger consortium from the Port of Veracruz exhibited a lower biodegradation rate of 3.77% and variable growth kinetics. Hydrocarbonoclastic bacteria identified within the consortia included Pseudomonas aeruginosa, Enterococcus faecalis, and Vibrio parahaemolyticus, among others. The hydrocarbonoclastic consortia have the potential to biodegrade from various forms of plastic waste, including single-use face masks.